Effects of Private Tuition, Time Allocation and Perceived Difficulty on Achievement in Mathematics of Secondary School Boys and Girls in Kerala - Abdul Gafoor K.; Sarabi M.K. (INDIAN EDUCATIONAL REVIEW, 2017)
This study examines the effect of gender, perceived difficulty, time allocation and private tuition on achievement in mathematics among secondary school students. A total of 988 students in grade nine from government and government-aided schools of Malappuram district of Kerala participated in the study. They completed a questionnaire on Mathematics Learning, and a grade-appropriate test of achievement. Results showed that whereas achievement in mathematics does not vary by gender, increase in perceived difficulty of mathematics adversely affects achievement. Students devoting less time on learning achieve significantly less. Private tuition is found to have positive impact on achievement in mathematics, especially of girls perceiving mathematics as highly difficult and among students allotting moderate time on learning mathematics at home. Even students perceiving high difficulty achieve better with moderate to high time allocation. The study suggested the need for putting efforts by students, teachers, parents and administrators to enhance the quality of students’ learning in mathematics.